Risk-Averse Monopolist with Aspiration - Serguei Kaniovski (Austrian Institute of Economic Research (WIFO), 2003)
This paper analyzes optimizing decisions of a monopolist under uncertainty. The aspiration model directly accounts for asymmetric risk preferences with respect to downside risk. The optimal output (price) of a risk-averse monopolist facing marginal cost uncertainty will not exceed that of his risk-neutral counterpart, and will be lower (higher) for realistic aspiration levels. This result is consistent with studies conducted in the traditional expected utility framework.
Keywords: D81; L12; L21; 330; Aspiration; Downside Risk; Monopoly; Risk-Aversion; Risikoaversion; Monopol; Entscheidung unter Unsicherheit